2020
DOI: 10.1108/jcms-09-2020-0034
|View full text |Cite
|
Sign up to set email alerts
|

Is there any effect of ESG scores on portfolio performance? Evidence from Europe and Turkey

Abstract: PurposeThe purpose of this paper is to examine the performance of portfolios that are constructed based on environmental, social and governance (ESG) scores and consist of stocks located in Europe and Turkey.Design/methodology/approachIn order to form the portfolios, firstly all stocks are ranked in a descending way based on ESG-based (ESG, environmental, social and governance) scores, separately. Then, 10% of stocks with the highest scores are included in the “Top” portfolio and 10% of stocks with the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…The formation of a portfolio can be done from several basic calculation bases, such as research conducted by Zehir and Aybars (2020) which shows that the ESG portfolio can be used as the basis for calculating the portfolio selection for long-term investments. Source: data processed According to Dayanandan and Lam (2015), there are differences in portfolio rebalancing strategies in US data.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of a portfolio can be done from several basic calculation bases, such as research conducted by Zehir and Aybars (2020) which shows that the ESG portfolio can be used as the basis for calculating the portfolio selection for long-term investments. Source: data processed According to Dayanandan and Lam (2015), there are differences in portfolio rebalancing strategies in US data.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the companies' ESG performance, we ranked their ESG scores by year and by country to arrive at three portfolios, namely: (i) Top ESG , the 10% of companies with the highest scores, (ii) Bottom ESG , the 10% of companies with the lowest scores, and (iii) No ESG , companies that did not report ESG information in the period. We assigned an equal share to each company, following Amon et al (2021) and Zehir and Aybars (2020). We repeated this process for each year from 2011 to 2019 to recompose the portfolios.…”
Section: Methodsmentioning
confidence: 99%
“…(iii) No ESG, companies that did not report ESG information in the period. We assigned an equal share to each company, following Amon et al ( 2021) and Zehir and Aybars (2020). We repeated this process for each year from 2011 to 2019 to recompose the portfolios.…”
Section: Responsible Investment Portfolios and Psychic Dividendsmentioning
confidence: 99%
“…Zehir and Aybars (2020) conducted their study in Europe and Turkey and found no association between SRI and portfolio performance. The CAPM analysis demonstrated that ESG-based portfolios are behind the market index.…”
Section: Literature Review and Hypothesesmentioning
confidence: 97%